EL USO DE LA NATURALEZA COMO SÍMBOLO AFECTIVO DE UN ESPACIO ARTÍSTICO ICONOGRÁFICO - GUZMÁN, ALICIA M.; DATSCHKE, OMAR E.; DIEMINGER, CARMEN M.; LOPEZ, RAQUEL A.; MENDOZA, NATALIA; NÚÑEZ, DARÍO G.; PELLIZZER, MARY M. (Salão do Conhecimento, 2013)
Resumo